1984
DOI: 10.1017/s0021859600043355
|View full text |Cite
|
Sign up to set email alerts
|

The effects of N fertilizer and soil moisture on the nodulation and growth ofPhaseolus vulgaris

Abstract: Soil water content affected the nodulation and N 2 fixation of Phaseolus vulgaris by Rhizobium phaseoli and the utilization of mineral N by plants. Plants grown in wet soil produced twice as much as those grown on dry soils. Nodule weight and activity were five to ten times greater than those from dry soils. At 45 days, N additions inhibited nodulation, but this effect was partially diminished in wet soils.The maximum N utilization from fertilizer to produce dry matter did not correspond to maximum N utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
(6 reference statements)
1
6
0
1
Order By: Relevance
“…Nodule fresh weight was lower on both levels of stress for Carioca, with decreases of 52% and 60% for five and eight day stresses, respectively ( Table 1). Saito et al (1984) also observed a sharp decrease in nodule fresh weight for cultivar Carioca under two levels of water stress. Nodule fresh weight in EMGOPA-201 was not affected by stress treatment.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Nodule fresh weight was lower on both levels of stress for Carioca, with decreases of 52% and 60% for five and eight day stresses, respectively ( Table 1). Saito et al (1984) also observed a sharp decrease in nodule fresh weight for cultivar Carioca under two levels of water stress. Nodule fresh weight in EMGOPA-201 was not affected by stress treatment.…”
Section: Resultsmentioning
confidence: 68%
“…After being harvested, plants were dried at 65 o C and grounded for determination of N concentration, using a Analyzer (Model 1106). Leaf water potential (LWP) was measured in the youngest fully most expanded leaf, using a pressure bomb (Scholander et al, 1965). Relative water content was measured in one leaflet just below the youngest expanded leaf.…”
Section: Methodsmentioning
confidence: 99%
“…An extended period of stress during the vegetative stage retards nodulation and depresses N 2 fixation (Abdel Ghaffar et al, 1982;Saito et al, 1984;Zablotowicz et al, 1981). Once the nodules are established, desiccation results in decreased N 2 fixation (Pankurst and Sprent, 1975), and it drops to near zero when nodule moisture content is reduced to 50 or 55%.…”
Section: Introductionmentioning
confidence: 99%
“…3 also shows that lucerne plants can support a minimum sitona weevil population density of about 1000/m 2 during drought. Saito et al (1984) observed that nodule weight of Phaseolus vulgaris plants in dry soil is about 10-20% of that in wet soil. Observations suggest that lucerne behaves in a similar way (Goldson unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Saito et al (1984) showed that nodule weight and activity in Phaseolus vulgaris L. can be reduced by up to 90% in dry soil. Hoglund (pers.…”
Section: Introductionmentioning
confidence: 99%